Encouraging Brand Evangelism Through Failure Attribution and Recovery Justice: The Moderating Role of Emotional Attachment - Zhu, Tingting; Park, Sung Kyu (Frontiers in Psychology, 2022)
Brand evangelism is essential to the profitability of e-shops, but the effects of failure attribution and recovery justice in encouraging brand evangelism in the online service recovery context are not straightforward. Grounded on a framework integrating Attribution theory, Justice theory and Attachment theory, this study explores whether failure attribution and recovery justice affect brand evangelism through recovery satisfaction with emotional attachment as a moderator. We gathered 400 samples from e-shoppers who encountered a service failure and recovery in the past year to verify the hypotheses using structural equation modeling and multiple-group analysis. Results declare that failure attribution (locus, stability and controllability) and recovery justice (distributive, procedural and interactional justice) are significantly related to recovery satisfaction and subsequent brand evangelism. Moreover, failure attribution (locus, stability and controllability) correlates significantly with recovery justice (distributive, procedural and interactional justice). In addition, emotional attachment plays a moderating role on the relationships between distributive and procedural justice on recovery satisfaction. This work contributes to brand evangelism research by giving a different perspective (i.e., service recovery) to comprehend what stimulate or deter brand evangelism. In addition, this work develops service recovery research through the combination of the third dimension of attribution (locus) and fourth dimension of justice (informational justice) into a framework, investigating the effect of failure attribution on recovery justice, and revealing the moderating effect of emotional attachment in the recovery process.